Solar Radiation (IntechOpen, 2025)
This book provides up-to-date, comprehensive insights into recent innovations and advancements in enabling technologies for the energy transition, with a particular emphasis on solar photovoltaic applications. It also covers essential, modern, and contemporary knowledge of digitalization and innovation in the energy transition. Key topics include: •Fundamental principles of electrification, decentralization, and flexibility concepts in energy transition •AI techniques and innovative approaches for solar radiation forecasting and solar photovoltaic energy optimization •Recent advances in solar photovoltaic technologies and applications, including solar energy system integration, solar photovoltaic plants, and integrated photovoltaics This book serves as a valuable reference for undergraduate and postgraduate students, as well as for both emerging and seasoned researchers, designers, and industrial engineers in the solar energy sector.